2012
DOI: 10.1371/journal.pgen.1002993
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Synaptonemal Complex Grows Continuously during Meiotic Prophase in Budding Yeast

Abstract: The synaptonemal complex (SC) links two meiotic prophase chromosomal events: homolog pairing and crossover recombination. SC formation involves the multimeric assembly of coiled-coil proteins (Zip1 in budding yeast) at the interface of aligned homologous chromosomes. However, SC assembly is indifferent to homology and thus is normally regulated such that it occurs only subsequent to homology recognition. Assembled SC structurally interfaces with and influences the level and distribution of interhomolog crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 46 publications
10
83
0
Order By: Relevance
“…Recently Voelkel-Meiman et al (54) examined SC dynamics in yeast meiosis by inducing Zip1-GFP expression in cells that have already assembled SC. Under these conditions they observed a nonuniform pattern of Zip1-GFP localization on the SC and concluded that the SC grows continuously in meiotic prophase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Voelkel-Meiman et al (54) examined SC dynamics in yeast meiosis by inducing Zip1-GFP expression in cells that have already assembled SC. Under these conditions they observed a nonuniform pattern of Zip1-GFP localization on the SC and concluded that the SC grows continuously in meiotic prophase.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in the literature has shown that the SC is not a static structure and can be constantly remodeled, for example, in response to DSB formation and repair (Couteau and Zetka 2011;Voelkel-Meiman et al 2012). This remodeling could be highly achievable by modifications at the N termini of central region components of the SC, as shown in this study.…”
Section: Roles Of N-terminal Acetylation In Sc Assemblymentioning
confidence: 99%
“…This is in contrast to delayed disassembly of RAD-51 on unpaired autosomes in smc-6 mutants ( Figure 5 and Figure S2), indicating that the X chromosome is unique in its lack of requirement for the SMC-5/6 complex. SC polymerization is dynamic, processive, and has a propensity to assemble on any available substrate (Voelkel-Meiman et al 2012). What then removes SYP-1 specifically from the X chromosome at the onset of pachytene, well before it is disassembled from autosomes?…”
Section: Sister Vs Homolog Interactions and Meiotic Dsb Formationmentioning
confidence: 99%